(untitled) (Academia Journal of Medicine, 2024)
The objective is to evaluate the instrumentation time required for primary molar root canal preparation using two pediatric rotary file systems (Kedo-S Plus & Fanta AFTM Baby) in comparison to manual K-files. 60 lower primary molars of healthy youngsters, ages 4-8 years were participated. Three groups (n=20) received a random assignment of molars. Kedo-S Plus and Fanta AFTM Baby rotary systems were used to prepare groups I and II, while a manual K file was used to organise group III, stopwatch was used to estimate the instrumentation time. The result shows that the first group had the lowest instrumentation time (78.8 seconds), followed by group II and the manual-K file group (p<0.05). Thus, the tested rotary file systems required less instrumentation time.